Vitiligo: Clinical Implications and Cell Line Models for Formulation Evaluation - Dr. Anupriya Kapoor, (Asian Journal of Pharmaceutics (AJP), 2025)
A chronic autoimmune disorder called vitiligo, with a prevalence rate of 0.004–2.28, is encouraged worldwide and is characterized by increasing skin pigmentation loss due to melanocyte destruction, resulting in depigmented skin patches. There are two primary categories of this condition: Segmental Vitiligo (SV), which is less prevalent and usually only affects one side of the body, and Non-SV, the most pervasive form and frequently associated with other autoimmune disorders. An autoimmune reaction that targets melanocytes is the outcome of the delicate interaction between genetic susceptibility and environmental variables in the pathophysiology of vitiligo. The clinical evaluation and family history are the basis for the diagnosis, which might additionally include skin biopsies and blood tests for assessing melanocyte loss. Vitiligo has a major psychological influence on one’s quality of living and can cause problems, including fret, low self-esteem, and social stigma. This summary highlights the necessity of having a thorough awareness of vitiligo to enhance management techniques and assist those suffering.